Signalling Sites of Contention in Judicial Discourse. An Exploratory Corpus- Based Analysis of Selected Stance Nouns in US Supreme Court Opinions and Poland’s Constitutional Tribunal Judgments - GOŹDŹ-ROSZKOWSKI, Stanisław (Comparative Legilinguistics, 2017)
This paper adopts a comparative, corpus-based perspective to examine the language of judicial justification. Based on substantial corpus data, the study explores one of the linguistics resources, i.e. head nouns (e.g. assumption, belief, notion, etc.) followed by a nominal complement in the form of that-clause in two comparable legal settings: the opinions given in the United States Supreme Court and the judgements handed down by Poland’s Constitutional Tribunal. The findings corroborate the results of previous research which shows that nouns found in this pattern are used to perform various discourse functions but evaluation plays a central role in judicial writing and these nouns are used to signal sites of contentions. The study reveals the general similarity between the two sets of data suggesting that American and Polish judicial writing is underpinned by essentially the same epistemological assumptions. Yet, there are some differences in the way the nouns behave phraseologically. Polish nouns tend to show less collocational variation and they are found performing fewer discourse functions.